Hydraulic effects of underground nuclear explosions, Amchitka Island, Alaska - Gonzalez, Don Diego, author; Nordin, Carl F., Jr., advisor; Richardson, Everett V., committee member; Waltz, James P., committee member; Longenbaugh, Robert A., committee member (Colorado State University. Libraries, 1977)
An intensive field study was undertaken as part of the U.S. Geological Survey Nuclear Hydrology Program to determine the response of drainage basins and groundwater aquifers to underground nuclear explosions. Measurements of streamflow and groundwater fluctuation were made over the period of underground nuclear testing on Amchitka Island. These observations were only minimal for the Long Shot event in 1965 but were expanded considerably for the Milrow and Cannikin events in 1969 and 1971, respectively. A conceptual model describing the phenomena that relates surface water and groundwater reaction to ground shock, was confirmed when field data supported the main features of the model. Slapdown, an effect of rock failure in tension, results in the greatest response during the event, the effects generally dissipating soon after their occurrence; however, the effects of cavity collapse are long lasting and, in many respects, permanent. Drainage areas surrounding ground zero as well as the groundwater reservoirs beneath them have undergone permanent changes. Distant groundwater effects are documented and are attributed to changes in aquifer porosity as a result of seismic response generated by the explosions. The most outstanding hydrological feature on Amchitka Island, Cannikin Lake, is a result of the collapse of the Cannikin cavity.
Keywords: Underground nuclear explosions -- Environmental aspects -- Amchitka Island; Cannikin Project